Transthyretin, Immature Platelet Fraction, and Mean Platelet Volume in Normotensive and Preeclampsia Pregnancy - Asri Ragil Kemuning; Herniah Asti Wulanjani; I Edward Kurnia Setiawan Limijadi; Indranila Kustarini Samsuria; Banundari Rachmawati (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Transthyretin protein experiences misfolding and aggregation in preeclampsia due to placental ischemia and inflammation. Placental endothelial damage occurring in preeclampsia stimulates the production of larger young platelets in the bone marrow and can be reflected by an increase in the immature platelet fraction (IPF) and mean platelet volume (MPV). Since the change in these markers in preeclampsia remains controversial, this study was conducted to analyze the differences in levels of transthyretin, IPF, and MPV as easily accessible markers in normotensive and preeclampsia pregnancies.METHODS: Total subjects included in this study were 32 normotensive and 26 preeclampsia pregnant woman. The measurement of serum transthyretin level was using enzyme-linked immunosorbent assay (ELISA) method. Meanwhile, IPF and MPV levels were measured by using a hematology analyzer with flowcytometry method. Data was statistically analyzed using unpaired T-test and Mann-Whitney, with significancy of p<0.05.RESULTS: Median value of transthyretin in normotensive and preeclampsia pregnancy were 11 (6-30) mg/dL and 9 (5-18) mg/dL. The mean value of IPF in normotensive and preeclampsia pregnancy were 4.56±2.19% and 6.33±2.99%. Mean value of MPV in normotensive and preeclampsia pregnancy were 10.41±0.76 fL and 11.32±1.2 fL. There were significant differences in levels of transthyretin, IPF, and MPV between normotensive and preeclampsia pregnancies (p=0.008, p=0.017, and p=0.002, respectively).CONCLUSION: There are significant differences in transthyretin levels, IPF, and MPV values in normotensive and preeclampsia pregnancies. Therefore, serum transthyretin, IPF, and MPV can be developed as affordable parameters for the diagnosis of preeclampsia.KEYWORDS: preeclampsia, transthyretin, IPF, MPV